Topical Ingenol Mebutate: A New Treatment Modality for Multiple Actinic Keratoses and Field Cancerization - Kostovic, Kresimir; Jerkovic Gulin, Sandra; Bukvic Mokos, Zrinka; Ceovic, Romana (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Ingenol mebutate gel is a recent stirring weapon recommended for the treatment of multiple actinic keratoses (AKs) and field cancerization. This review brings a summary of recent data on the treatment of AKs with ingenol mebutate (IM) providing critical commentary with regard to drug's characteristics, drug's safety profile, treatment regimen, treatment outcome, patient compliance, AK recurrence, costeffectiveness and cost-utility, as well as guidelines for the management of the treatment of AK. Method: We undertook a structured search of bibliographic databases for peer-reviewed scientific articles, including review articles, original research articles as well as case report articles based on inclusion/exclusion criteria. Reports on ingenol mebutate from U.S. Food and Drug Administration and European Medical Agency were also included. Results: Sixty-six papers were included in this review. We report current data on ingenol mebutate chemical properties, pharmacology, efficacy, safety, and tolerability, potential new indications in dermatology, costeffectiveness, and cost-utility analysis. Conclusion: Treatment of AKs is necessary in order to prevent possible transition to invasive SCC. Although the mechanism of action of ingenol mebutate is not fully elucidated, dual mechanism of action is presumed. Ingenol mebutate is an effective and cost-saving topical agent for the treatment of AK, especially multiple AKs and field cancerization, with acceptable safety profile. It may also have perspective in dermatology regarding the treatment of superficial BCC, Bowen disease, actinic cheilitis, and anogenital warts that has to be evaluated in clinical trials. Patients' adherence to recommended treatment regimen and auspicious safety profile make this drug attractive.
Keywords: Euphorbia peplus